2010
DOI: 10.1021/jf101209g
|View full text |Cite
|
Sign up to set email alerts
|

National Study of Exposure to Pesticides among Professional Applicators: An Investigation Based on Urinary Biomarkers

Abstract: Epidemiologic studies of pesticides have been subject to important biases arising from exposure misclassification. Although turf applicators are exposed to a variety of pesticides, these exposures have not been well characterized. This paper describes a repeated measures study of 135 TruGreen applicators over three spraying seasons via the collection of 1028 urine samples. These applicators were employed in six cities across the United States. Twenty-four-hour estimates (μg) were calculated for the parent comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Similar to our study, when samples were spread over time (2 weeks to 1 year), ICCs were low (0.02–0.3), indicating a strong contribution of within-person variability (Griffith et al 2011; Harris et al 2010; Meeker et al 2005; Sexton and Ryan 2012; Whyatt et al 2009). These low ICCs were observed across different exposure scenarios: occupational parental exposure, residence in proximity to agricultural fields, and urban and suburban general population level exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Similar to our study, when samples were spread over time (2 weeks to 1 year), ICCs were low (0.02–0.3), indicating a strong contribution of within-person variability (Griffith et al 2011; Harris et al 2010; Meeker et al 2005; Sexton and Ryan 2012; Whyatt et al 2009). These low ICCs were observed across different exposure scenarios: occupational parental exposure, residence in proximity to agricultural fields, and urban and suburban general population level exposure.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies reported that oxidative stress caused by testicular tissue and lymphocyte in semen will impair sperm parameters [24], [27], suggesting that owing to lack of lymphocytes around, “swim-up” mouse spermatozoa in our study are more resist to the exposure of nicotine than human spermatozoa in semen. Human exposure to neonicotinoids is very limited (12.8–350 ng/ml in the urine of farm workers, with or without protection) [28], [29], our study indicated that, at exposure levels, IMI and ACE do not show adverse effects on mouse sperm functions and early embryo development in vitro (data not shown). However, recent animal studies showed that IMI and ACE could cause oxidative stress in body [5], [26], and even chronic exposure of IMI with a low concentration could result in oxidative stress in tissues [30], which warned that low level of neonicotinoid exposure in a long period may also exert impacts on reproduction of human, especially for professional populations.…”
Section: Discussionmentioning
confidence: 64%
“…The unprotected turf applicators of liquid 2,4-D had the highest urinary levels reported in a controlled study (Harris et al, 1992). The highest levels in another turf study were observed during the spring season, compared to the summer and fall (Harris et al, 2010). Other exposure studies of professional turf applicators reported internal dose estimates and are not directly comparable to the studies in Table 3 (Harris et al, 2002, 2005).…”
Section: Review Of Urinary Biomonitoringmentioning
confidence: 93%